Webinar “War On Drugs Mahasiswa Cerdas Jaga Kesehatan Mental Cegah dan Jauhi Narkoba” - Wira Santika, Wira Santika; Sriwijayanti, Anastasya Indah; Riyanto, Agustinus (Communautaire: Journal of Community Service, 2022)
The purpose of this community service is to increase publicawareness about the dangers of drug abuse for mentalhealth. The method used in this community service is a zoommeeting as an educational medium for the webinar "War OnDrugs, Smart Students Take Care of Mental Health, Preventand Stay Away from Drugs." Based on the results of the pretest followed by the participants, in the first question, asmany as 49.5% of respondents know substances that causestimulant effects. As many as 50.5% of respondents still donot know drugs that cause stimulant effects. In the secondquestion, 59.7% of webinar participants already know whatsubstances or drugs from plants or non-plants can cause adecrease and change in consciousness, loss of pain, and causedependence. Moreover, as many as 40.3% still do not knowsubstances or drugs from plants or not from plants that cancause decreased and altered consciousness, loss of pain, andalso cause dependence. The post-test results showed thatmore participants knew the impact of drug abuse on mentalhealth. This means that there is a significant differencebetween public knowledge before and after being giveneducation about the impact of drug abuse on mental health.